Long‐term drivers of vegetation turnover in Southern Hemisphere temperate ecosystems. Issue 2 (5th December 2020) - Adeleye, Matthew Adesanya; Mariani, Michela; Connor, Simon; Haberle, Simon Graeme; Herbert, Annika; Hopf, Felicitas; Stevenson, Janelle
Abstract: Aim: Knowledge of the drivers of ecosystem changes in the past is key to understanding present ecosystem responses to changes in climate, fire regimes and anthropogenic impacts. Northern Hemisphere‐focussed studies suggest that climate and human activities drove turnover during the Holocene in temperate ecosystems. Various drivers have been invoked to explain changes in Southern Hemisphere temperate vegetation, but the region lacks a quantitative assessment of these drivers. To better understand the regional drivers of past diversity, we present a quantitative meta‐analysis study of turnover and richness during the lateglacial and Holocene in Australian temperate ecosystems. Location: South‐east Australia (Tasmania, Bass Strait, SE mainland). Methods: We conducted a meta‐analysis study of 24 fossil pollen records across south‐east Australian temperate ecosystems, applying an empirical turnover threshold to fossil records to identify periods of major turnover for the first time in Australia. We tested pollen richness as a proxy for vegetation richness to estimate past richness and applied this to fossil pollen data. The resulting reconstructions were compared to independent records of climate, sea‐level change and fire through generalized linear modelling. Results and conclusion: Our results show changes in available moisture and sea level drove turnover and richness in most parts of SE Australia in the past, explaining up to c.  97% deviance. However, fire mainly drove turnover in Bass Strait. Our richness reconstructions also support the intermediate disturbance hypothesis, suggesting that high biodiversity was partially maintained by anthropogenic‐managed fire regimes. While temperature change is considered key to Northern Hemisphere palaeodiversity, past turnover and richness in Southern Hemisphere temperate ecosystems responded mainly to moisture availability and sea‐level change (considering its role in modulating regional oceanic climate).